2023
DOI: 10.1186/s12882-023-03320-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of patients receiving maintenance hemodialysis regarding hemodialysis and its complications: a single-center, cross-sectional study in Nanjing

Fangfang Xu,
Bing Zhuang,
Zhongxia Wang
et al.

Abstract: Background Good knowledge of and attitudes toward hemodialysis and its complications might be expected to promote good practices and improve adherence. This study investigated, the knowledge, attitude, and practice of patients receiving hemodialysis regarding hemodialysis and its complications. Methods This cross-sectional study enrolled patients with uremia who were receiving hemodialysis at the Second Affiliated Hospital of Nanjing Medical Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…It shows that 60.3% possessed excellent knowledge, and there was statistical significance with income and education on renal diet with a p-value <0.001. However, in our study, these variables were not statistically significant [19].…”
Section: Discussioncontrasting
confidence: 78%
“…It shows that 60.3% possessed excellent knowledge, and there was statistical significance with income and education on renal diet with a p-value <0.001. However, in our study, these variables were not statistically significant [19].…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies have shown that self-care in hemodialysis patients is significantly correlated with knowledge and self-efficacy [10], and that knowledge of hemodialysis and self-care behaviorare positively correlated [11]. Topics related to hemodialysis include kidney function, blood vessel management, medication management, dialysis, exercise, and daily routines [12]. Improving treatment knowledge is important to ensure effective disease management [13].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Improving treatment knowledge is important to ensure effective disease management [13]. Prior research has shown that self-care behavior improves in hemodialysis patients when they acquire accurate knowledge about dialysis and disease managementand build self-efficacy [12]. A study on older hemodialysis patients found that increased self-efficacy encourages them to stay on life support and prevents further deterioration in their health [14].…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the dietary KAP status of HD patients could help health professionals identify weaknesses in dietary management and develop corresponding interventions to improve patients’ dietary practice. Although a previous single-center survey investigated the KAP regarding hemodialysis and its complications in HD patients, it did not include dietary-related questions [ 18 ]. Therefore, more studies are needed to investigate the dietary KAP status of HD patients.…”
Section: Introductionmentioning
confidence: 99%